Elephant census in the Ankasa Conservation Area in south-western Ghana - Danquah, Emmanuel; Boafo, Yaw; Dubiure, Umaru; Nandjui, Awo; Hema, Emmanuel; Appiah, Mildred (Pachyderm, 2001)
Results from a dry season dung count carried out during January 2001 in Ankasa Conservation Area estimate a population of approximately 21 elephant. Most of the animals were found in the vicinity of the Suhien River. A pre-study reconnaissance had statified the areas into three stata, low, medium and high, based on assumed density. However, the study suggests it would be better to have a two stata system and arrange the high density stratum along the Suhien River. All 43 dung piles observed were on the 16 transects in the high density strata near the River. This 509 sq km Conservation Area which covers the two adjacent forests of Nuni-Suhian NP and the Ankasa Resource Reserve in southwestern Ghana appears to house the smallest elephant population in Ghana’s forest zone. It is an important plant diversity region and has been only lightly logged thus far. It is important to monitor the elephant population in order to assess whether it is isolated or if the estimated 21 elephant move between Ankasa and the Draw River FR.